Manejo general del intoxicado - Quezada I., Ricardo; Espinoza Z., Carolina; Fuentes N., Rosario (Revista Hospital Clínico Universidad de Chile, 2014)
Intoxications have become a relevant complaint in the emergency room since the second half of the last century. Toxidromes have been replaced by a more practical combined analysis of vital signs, directed physical examination and selected laboratory tests. Most of the mortality can be prevented by the correct and opportune implementation of general management strategies, including supportive care, prevention of absortion, enhancement of elimination and extracorporeal removal of toxins. Through the following pages we will review many of different diagnostic and therapeutic alternatives.